Acute and subacute effects of endotoxin on hypothalamic gaseous neuromodulators. - Kostoglou-Athanassiou, I; Jacobs, R; Satta, M; Dahia, P; Costa, A; Navarra, P; Chew, S; Forsling, M; Grossman, AB (1998)
Although two-way communication between the hypothalamus and the immune system in now well established, particularly for the hypothalamo-pituitary-adrenal axis, the role of the gaseous neurotransmitters nitric oxide (NO) and carbon monoxide (CO) is much less well understood in terms of hypothalamic function. These agents are an important part of the peripheral inflammatory response; and their synthetic enzymes, NO synthase (NOS) and heme oxygenase (HO), respectively, have been localized to the hypothalamic PVN and SON. The induced generation of both NO and CO leads to the suppression of CRH and vasopressin, the major stimulators of the HPA. Thus, the addition of hemin to hypothalamic explants is maximally active at 1 microM in attenuating the release of CRH and vasopressin, and this dose is also most effective in generating biliverdin and associated CO. CO generation is also able to stimulate cyclooxygenase to produce prostaglandin E2, an established intermediary in the cytokine-stimulated activation of the HPA. Finally, inducible NOS mRNA is specifically induced in the hypothalalmus in response to endotoxin, in parallel to interleukin-1. These data provide increasing evidence in favor of NO and CO as counterregulatory agents in the HPA response to immune activation.